2020
DOI: 10.1039/c9ta07700f
|View full text |Cite
|
Sign up to set email alerts
|

A sulfur-tolerant cathode catalyst fabricated with in situ exsolved CoNi alloy nanoparticles anchored on a Ruddlesden–Popper support for CO2 electrolysis

Abstract: The schematic of CO2 electrolysis to produce CO in an SOEC under the conditions of CO2 gas containing H2S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 55 publications
0
37
0
Order By: Relevance
“…Thus, these phases could recombined, giving the exsolved nanoparticles the ability to re‐dissolve depending on the gas environment, which in turn leads to materials with high durability due to the fact that they can regenerate. This applies both for single metals [12] as well as for bimetallic systems [6d, 7g, h, 10, 11c, e, 13] . For example, Fe−Co nanoparticles from La 0.3 Sr 0.7 Cr 0.3 Fe 0.6 Co 0.1 O 3‐δ were found to completely redissolve into the perovskite when re‐oxidized at 800 °C while they remained on the surface as transition‐metal oxide at 700 °C [7g] .…”
Section: Bimetallic Alloy Nanoparticle Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these phases could recombined, giving the exsolved nanoparticles the ability to re‐dissolve depending on the gas environment, which in turn leads to materials with high durability due to the fact that they can regenerate. This applies both for single metals [12] as well as for bimetallic systems [6d, 7g, h, 10, 11c, e, 13] . For example, Fe−Co nanoparticles from La 0.3 Sr 0.7 Cr 0.3 Fe 0.6 Co 0.1 O 3‐δ were found to completely redissolve into the perovskite when re‐oxidized at 800 °C while they remained on the surface as transition‐metal oxide at 700 °C [7g] .…”
Section: Bimetallic Alloy Nanoparticle Systemsmentioning
confidence: 99%
“…Ni−Co exsolution studies mostly refer to electrochemical applications, [7h–j] in which these particles demonstrate similar characteristics to those of their Fe based counterparts (Section 3.1 and 3.2). Recently, it was reported that an anode material based on Ni−Co alloy nanoparticles exsolved from La 0.52 Sr 0.28 Ti 0.94 Ni 0.03 Co 0.03 O 3‐δ exhibited high catalytic activity towards NH 3 decomposition and H 2 oxidation due to the abundant active sites and the balanced NH 3 adsorption and N 2 desorption process ascribed to the synergistic effects of Ni and Co in the alloy.…”
Section: Bimetallic Alloy Nanoparticle Systemsmentioning
confidence: 99%
“…Sol–gel is another prominent synthesis technique used (sol–gel synthesis was employed in 41% of the papers covered by this review), which allows for phase formation at temperatures as low as 700 °C hence producing much smaller grains (tens to hundreds of nanometers). [ 56,57 ] Therefore, a variety of sol–gel routes, including the citrate‐based [ 35 ] EDTA/citrate‐based, [ 58,59 ] and Pechini methods, [ 60,61 ] have been extensively employed to synthesize perovskites for both catalytic and electrochemical applications. Moreover, the combustion method is often used, where glycine, [ 62 ] citric acid, [ 63 ] or both [ 64 ] are added in the solution of metal nitrate precursors as both complexing agents and fuel.…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…In addition to the electrolysis of pure CO 2 , some literature also reported that an amount of CO in CO 2 gas can help in preventing the oxidation of metal phases and improving the performance of CO 2 electrolysis. [ 81,101,118,120,150,155 ] For example, the ratio of CO to CO 2 was reported to impact SOEC performance. Using (La 0.3 Sr 0.7 ) 0.9 Ti 0.9 Ni 0.1 O 3− δ (LSTN) with Ni metal nanoparticles as the cathode, Gan et al.…”
Section: Performance Of Exsolution Materials For the Conversion Of Smmentioning
confidence: 99%
“…As shown in Table 4 , these reported exsolution materials include single metal particles composed of Ni, [ 68,115–122 ] Cu, [ 92 ] Co, [ 81 ] Fe, [ 135–137 ] and Rh. [ 108 ] Such materials also encompass alloys, such as Fe–Ni, [ 101,102,144,145 ] Ni–Cu, [ 105,152 ] Co–Ni, [ 150 ] and Co–Fe. [ 101,154–156 ] For the electrolysis of pure CO 2 gas, exsolution materials were generally used as the cathode electrodes of SOECs.…”
Section: Performance Of Exsolution Materials For the Conversion Of Small Moleculesmentioning
confidence: 99%